An Investigation of Medial Tibial Component Overhang in Unicompartmental and Total Knee Replacements Using Ultrasound in the Outpatient Department - Mortensen, Jacob F.; Hald, Julius T.; Rasmussen, Lasse E.; Østgaard, Svend E.; Odgaard, Anders (The Journal of Knee Surgery, 2021)
Tibial component overhang is known to be a contributor to worse outcomes in knee arthroplasty. The aim of this study is to investigate the presence of tibial component overhang, and whether overhang correlates to a higher local tenderness in both medial unicompartmental and total knee replacements. Also, to determine if a rotational projection phenomenon is presented with radiographs when investigating tibial component overhang. A prospective study, including 64 participants, was performed, where ultrasound measurements were compared with postoperative radiographs. Local tenderness was measured as a pressure pain threshold, determined at 3 months postoperatively using algometry. Sixty-two of sixty-four patients had an underdiagnosed medial overhang on radiographs, with a mean difference of 2.4 mm between radiographs and ultrasound (p < 0.001), presenting a rotational projection phenomenon. When comparing sites with ultrasound measured overhang to sites without overhang measured by ultrasound, a higher local tenderness was observed (p < 0.001). A positive linear correlation was found between patients' overhang and local tenderness (r = 0.2; p = 0.045). Subgroup analysis of medial overhang showed significantly higher tenderness than all other locations. No significant differences were seen for lateral overhang. An apparent rotational projection phenomenon of overhang on radiographs was seen, and a linear association between overhang and local tenderness was demonstrated. This study warrants the use of ultrasound when a surgeon is presented with a patient with postoperative medial tenderness, but no overhang can be seen on radiographs. It should also raise awareness of implant selection and positioning during surgery, especially avoiding the overhang to be localized directly medially.
Keywords: knee; arthroplasty; ultrasound; overhang; radiography